Preparation and Characterisation of Laminated Fibre-Reinforced Polypopylene/Ethylene Vinyl Acetate/Organoclay Composites - Kamarudin, Siti Hasnah (2011)
There is an increasing need to investigate more environmental friendly, sustainable materials to replace existing materials as industry attempts to lessen the dependence on petroleum based fuels and products. The natural fibre composites offer specific properties comparable to those of conventional fibre composites. This research focused on preparation and characterisation of laminated kenaf fibre reinforced polypropylene (PP)/ethylene vinyl acetate (EVA)/organoclay composites. Effect of organoclay and EVA loading on the properties of PP/EVA/clay composites were characterized. Furthermore, effect of kenaf fibre on properties of laminated kenaf fibre reinforced polypropylene (PP)/ethylene vinyl acetate (EVA)/organoclay composites was also studied. In this study, polymer/clay composites from polypropylene (PP), organoclay and ethylene vinyl acetate (EVA) were prepared using a Brabender twin screw extruder and pelletized. The composites pellets were then laminated with kenaf fibres before being put into hot and cold press. The composites were characterized using Thermogravimetric analysis (TGA), Dynamic mechanical analysis (DMA), Instron machine and Transmission Electron Microscopy (TEM). The presence of clay and EVA in PP/clay composite improved the thermal stability as shown by thermogravimetric analysis (TGA). DMA studies established that EVA led to decrease of stiffness of the composite. The properties of composite with organoclay showed an improvement in tensile strength, tensile modulus, flexural strength and flexural modulus. However, the reduction in impact strength for the PP/clay composite was observed. The tensile and flexural strength of PP/clay composite decreased while impact strength increased with the addition of EVA. TEM micrographs show that the composite types were intercalated. PP/clay composite with 5 phr EVA loading showed the optimum mechanical and physical properties. Laminated kenaf reinforced composites were examined by Instron machine, Shinho Thermal Conductivity machine, and Scanning Electron Microscopy (SEM). The amount of water absorption rate decreased with the addition of organoclay and EVA to kenaf fibre reinforced PP composites. The mechanical properties such as tensile, flexural and impact strength are compared between PP/EVA/clay composite reinforced kenaf fibre and PP/EVA/clay composite without kenaf fibre. All the composites reinforced kenaf fibre showed higher mechanical properties compared to the composites without kenaf fibre. Incorporation of kenaf fibre to the composites increased heat insulator behaviour by reducing the value of thermal conductivity. SEM micrographs gave clear indication of the effect of EVA in reduction of void sizes and numbers, and close interaction of PP/clay and fibre was clearly demonstrated for composite with elastomer.